Effects of resistance exercise combined with vascular occlusion on muscle function in athletes - Takarada, Y.; Sato, Y.; Ishii, N. (European Journal of Applied Physiology, 2002)
. The effects of resistance exercise combined with vascular occlusion on muscle function were investigated in highly trained athletes. Elite rugby players (n=17) took part in an 8 week study of exercise training of the knee extensor muscles, in which low-intensity [about 50% of one repetition maximum] exercise combined with an occlusion pressure of about 200 mmHg (LIO, n=6), low-intensity exercise without the occlusion (LI, n=6), and no exercise training (untrained control, n=5) were included. The exercise in the LI group was of the same intensity and amount as in the LIO group. The LIO group showed a significantly larger increase in isokinetic knee extension torque than that in the other two groups (P<0.05) at all the velocities studied. On the other hand, no significant difference was seen between LI and the control group. In the LIO group, the cross-sectional area of knee extensors increased significantly (P<0.01), suggesting that the increase in knee extension strength was mainly caused by muscle hypertrophy. The dynamic endurance of knee extensors estimated from the decreases in mechanical work production and peak force after 50 repeated concentric contractions was also improved after LIO, whereas no significant change was observed in the LI and control groups. The results indicated that low-intensity resistance exercise causes, in almost fully trained athletes, increases in muscle size, strength and endurance, when combined with vascular occlusion.